Assessing UN Women's contribution to addressing sexual violence in public spaces through the Safe Cities and Safe Public Spaces program in Vietnam (Jurnal Anifa: Studi Gender dan Anak, 2026)
Sexual violence against women and girls in public spaces remains a persistent challenge in Vietnam despite various national and international intervention efforts. This study examines the contribution of United Nations (UN) Women in addressing sexual violence in public spaces through the Safe Cities and Safe Public Spaces Program during the 2017–2025 period. A descriptive qualitative approach was employed using secondary data collected from reports, policy documents, and relevant publications. The data were analyzed through data reduction, categorization, interpretation, and conclusion drawing. The findings show that UN Women's contribution is manifested through integrated interventions implemented under the Safe Cities and Safe Public Spaces Program. Among these interventions, improvements in public infrastructure and integrated survivor services have made the greatest contribution to enhancing public safety and expanding survivors' access to support services. In contrast, capacity-building initiatives involving workshops, men's engagement, and collaboration with educational institutions require sustained implementation to produce long-term behavioral change, while public awareness campaigns demonstrate relatively limited impact due to their short-term implementation. The study concludes that UN Women has made a significant contribution to strengthening public safety and survivor support systems in Vietnam. However, addressing the underlying social norms that perpetuate sexual violence requires sustained, collaborative, and multi-sectoral interventions involving government agencies, civil society organizations, educational institutions, and local communities.